(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Article in students vocals - chorus qualifications to form dedicated. In it to sing of qualifications theoretical basics with get to know one in line education in the process general didactic and special music of pedagogy main principles and their content - essence to students absorb